Socio-Informational Dynamics of Mis/Disinformation in Malaysia’s Digital Ecosystem: An Integrative Review - Lee, Kenneth Tze Wui; Sau, Zhi Xin (Universitas Muhammadiyah Sidoarjo, 2026)
The alarming surge of mis/disinformation in Malaysia reflects a form of information disorder shaped by the nation’s digital platform dynamics, ethno-political sensitivities, and contested legal responses. This nexus gives rise to distinctive socio-informational patterns in how false narratives are constructed, diffused, and addressed. Understanding these patterns is critical for effective intervention. This integrative literature review synthesizes findings from 15 peer-reviewed articles to identify and critically examine key socio-informational patterns. The study draws on interdisciplinary theoretical frameworks, including Diffusion of Innovations, Intergroup Threat, and Securitization theories, alongside the psychological concept of confirmation bias, to analyze how technological, psychological, and political factors influence Malaysia’s mis/disinformation landscape. Three emerging socio-informational patterns stand out: rapid digital diffusion of false content, instrumental use of identity-based narratives, and an ongoing struggle between securitized legal control and public resistance. The findings show that algorithm-driven amplification on social media platforms significantly accelerates the spread of mis/disinformation within Malaysia’s hyperconnected society. Besides, disinformation is strategically employed to amplify ethnic and religious divisions, a dynamic further intensified by emerging technologies such as AI-generated deepfakes, posing significant challenges to public trust, social harmony, and democratic resilience. While legislative tools like the Anti-Fake News Act 2018 have proven controversial and limited in effect, citizen-centric mitigation efforts, such as media and information literacy initiatives, are becoming increasingly recognized as more sustainable and practical solutions. The review concludes by calling for continuous, localized educational initiatives and future research that explores how community-driven interventions can strengthen information integrity in diverse societies.